RANCANG BANGUN SIMULATOR KAPAL MOTOR MENGGUNAKAN PANEL SURYA - Tharo, Zuraidah; Anisah, Siti; Hamdani, Hamdani; Ginting, Justra; Kusuma, Budhi Santri (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Solar power generation is one of the many renewable energies whose use has begun to develop until recently. In this case the use of solar panels is intended for boat / fishing boat simulators, which aim to provide technological innovation and use of natural resources as a substitute for petroleum fuels. Using solar panels, batteries, solar charge controllers and dc motors, a boat / fishing boat simulator is made that can operate during the day for about 2 hours, with a battery voltage of 5.11 volts and a current of 176 mA and at night it can only operate for about 15-20 minutes. with voltages below 3 volts and currents below 100 mA. To further maximize the system, we recommend using a solar panel and a larger battery